Neuroenhancement as Instrumental Drug Use: Putting the Debate in a Different Frame - Schleim, Stephan (Frontiers in Psychiatry, 2020)
The use of performance-enhancing drugs to study or work better is often called “cognitive enhancement” or “neuroenhancement” and sparked a debate between scholars from many disciplines. I argue that behavior of that kind can better be subsumed under the more general category of “instrumental drug use”. This broader perspective allows to understand neuroenhancement better from the perspective of addiction medicine and public health and supports a more consistent drug policy. I also summarize the most important systematic reviews and individual surveys of nonmedical substance use to study or work better. Different definitions and methodologies limit the comparability of these studies. The unified approach of drug instrumentalization would partially solve such problems. Finally, prevalence studies from the 1960s-1980s as well as anecdotal evidence since the late 19th century show that instrumental drug use is and has been for a long time a common phenomenon. It should thus also be investigated and treated consistently.